Demorest's Family Magazine - Demorest, William Jennings (New York: W. J. Demorest, 1882)
Demorest's Family Magazine. September 1882. Vol. 18, no. 11. -- Mascot, the Match-Maker -- Esther's Love Story -- The Queen -- The Poet's Vision -- Carmen Sylva -- The Two Gourmands -- The Rock of the Betrothed -- Talks with Women: The Girl of the Period -- Fort Snelling and Junction of the Mississippi and Minnesota -- Friedrich Frobel; His Life and Work -- A Soul to Heaven -- The Admiral's Ward -- Home Art and Home Comfort: Needle-work and Doyleys -- The Tambourine -- Enlarges Astor Library -- A Church Sociable -- Current Topics: Notes and Comments on Events of the Day -- The Baby's Name -- From the German -- Music Portfolio, or School Bag -- Pillow for Macrame Lace -- Fancy Stitches for Embroidery -- Work Bag -- Work for Invalids -- What Women are Doing -- Kitchen: Preserves, Jellies, Etc. -- Scientific -- Diamonds of Thought -- Spice Box -- Mirror of Fashion: Review of Fashions -- Illustrated Designs -- Black and White -- Early Autumn Wraps -- Odama Basque -- Aprons -- Dressy Lingerie -- A Wedding in the Country -- A Novel Fancy Fair -- Ladies Costumes -- Artistic Dresses -- Summer Fabrics -- Straw Parasols -- Out-Door Wear -- Misses' Costumes -- Dress in the Mountains -- Summer Shade Hats -- Children's Fashions -- Tina Dress
New York Illustrated News
Mme Demorest's Mirror of Fashions
Digitized from original print. Valdosta State University Archives and Special Collections. June 13, 2017.
Keywords: Dressmaking; Catalogue; Children; Illustrated Periodicals; Women's History; Social History; Homemaking; Needlework; Travel; 1800s; 19th Century; Magazine